Project-based learning as a means of forming leadership qualities in senior preschool children - G. Vatamaniuk; T. Tetiana (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
The relevance of this research is determined by the modern demands of Ukrainian society for the formation of motivated, responsible citizens who can successfully fulfil leadership roles. The aim of the study was to find an answer to the question of how project-based learning contributes to the development of leadership qualities in older preschool children. The research employed structural-functional, terminological, humanistic, genetic, activity-functional, and competency-based approaches, as well as general scientific logical methods (analysis, the unity of induction and deduction, modelling, and systematisation). Leadership qualities (independence, initiative, creativity, responsibility, communicativeness, organisational skills, partnership, empathy) were defined as components of leadership as a child’s social competence. It is shown that project-based learning involves the organisation of children’s activities to create a project, which is based on the need to solve a life problem, achieve a certain goal, to obtain a specific result through the sequential solution of current tasks. Project-based learning aligns with the demands of the modern age, expanding the space for children’s creativity, stimulating thinking, boosting motivation, and enabling educators and children to be partners, avoiding displays of dominance. Project-based learning successfully fosters leadership qualities such as communicativeness, organisational skills, partnership, and empathy in senior preschool children, as it is built on group interaction with its inherent phenomena of role distribution, communication, and mutual understanding. By modelling the process of solving real-life problems during the project, children develop leadership qualities such as independence, initiative, creativity, and responsibility. The specific capabilities of project-based learning in developing leadership qualities lie in providing opportunities for children to exhibit leadership qualities in interactions with both peers and adults; fostering various types of leadership (communicative and business, formal and informal, etc.) and the acquisition of different leadership roles (organiser, expert, idea generator, communicator); and preventing “negative” leader traits such as arrogance, dominance, and egocentrisms